Nfat/calcineurin signaling promotes oligodendrocyte differentiation and myelination by transcription factor network tuning - Matthias Weider (Nature Portfolio, 2018)
Oligodendrocyte differentiation is known to depend on transcription factors Sox10, Nkx2.2, and Olig2. Here, the authors show that Nfat/calcineurin signaling contributes to oligodendrocyte differentiation by relieving mutual repression of Nkx2.2 and Olig2.